Leading from the emerging future : from ego-system to eco-system economies - Scharmer, Claus Otto, 1961- (BK currents book., 2013)
Our Time Is NowWe have entered an age of disruption. Financial collapse, climate change, resource depletion, and a growing gap between rich and poor are but a few of the signs. Otto Scharmer and Katrin Kaufer ask, why do we collectively create results nobody wants? Meeting the challenges of this century requires updating our economic logic and operating system from an obsolete "ego-system" focused entirely on the well-being of oneself to an eco-system awareness that emphasizes the well-being of the whole. Filled with real-world examples, this thought-provoking guide presents proven practices f